PROFESSOR P.P. KOPNIAIEV - SCIENTIST, PUBLIC PERSON, ESTABLISHER OF HIGHER ELECTRICAL ENGINEERING EDUCATION (TO THE 150TH ANNIVERSARY OF HIS BIRTH) - V. B. Klepikov (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose. To carry out complete historical and scientific analysis of Professor P.P. Kopniaiev's activities and establish his role and place of achievements in the formation of the basic concepts and directions of the theory of electrical engineering and its practical application in the development of higher education in Ukraine. Methodology. We have applied general scientific methods of logic and classification, analysis and synthesis and special historical methods – historical-comparative, problem-chronological, synchronic and diachronic. Results. On the basis of generalization of a wide range of sources of central, regional and personal archives, the principles and content of scientific-pedagogical, organizational and public activities of P.P. Kopniaiev were revealed and the classification of the scientific work according to the main directions of his research was conducted. Originality. Complex analysis of P.P. Kopniaiev's scientific-pedagogical, organizational and public activities were carried out in the field of higher electrical engineering education and industrial development in Ukraine, and his scientific achievements were classified according to the main directions. Practical value. Factual information, generalizations and conclusions can be applied in the teaching of humanitarian and engineering disciplines in higher education, in particular in the development of the lecture courses and textbooks used in educational activities, as well as in the preparation of general and scientific works on the history of science and technology.